Teaching Prescribing: Just What the Doctor Ordered? A Thematic Analysis of the Views of Newly Qualified Doctors - Christina R. Hansen; Elaine K. Walsh; Colin P. Bradley; Laura J. Sahm (MDPI AG, 2017)
Undergraduate medical education has been criticised for failing to adequately prepare doctors for the task of prescribing. Pharmacists have been shown to improve medication use in hospitals. This study aims to elicit the views of intern doctors on the challenges of prescribing, and to suggest changes in education to enhance prescribing practice and potential role of the pharmacist. Semi-structured, qualitative interviews were conducted with intern doctors in their first year post qualification in an Irish hospital. Data collection was conducted until no new themes emerged and thematic analysis was performed. Thirteen interviews took place. Interns described training in practical prescribing as limited and felt the curriculum failed to convey the reality of actual prescribing. Pharmacists were perceived to be a useful, but underutilised, information source in the prescribing process. They requested an earlier introduction, and repeated exposure, to prescribing, and suggested the involvement of peers and pharmacists in this teaching. Intern doctors reported difficulties in applying knowledge gained in medical school to clinical practice. New strategies are needed to enhance the clinical relevance of the medical curriculum by rethinking the learning outcomes regarding prescribing practice and the involvement of pharmacists in prescribing education.